Konsep Pendidikan Literasi dalam al-Qur'an: Telaah atas Penafsiran M. Quraish Shihab dan Hamka terhadap Surat al-‘Alaq: 1-5 - Thoriq Aziz Jayana; Mansur Mansur (Ar-Raniry: International Journal of Islamic Studies, 2021)
This study investigated the concept of Quran-based literacy as the revelation first relegated called Surah Al-'Alaq: 1-5which evoked the spirit of literacy. However, it took efforts in contextualizing its verse to explore the concept of literacy extensively through the views of the commentators, which in this case adopted the interpretation of M. Quraish Shihab and Hamka. This study employed a descriptive-qualitative method with a literature review research design. The results of the study indicated that the concept of literacy in the Quran could be described in various ways aspects ranging from the interpretation of the meaning of iqra 'and al-qalam, purposes of literacy, the object of literacy, and manners in literacy according to Quranic values. Therefore, Allis essentially creates balance and continuity between mind, heart, and actions (think scientifically, show Sufistic spirit, and have productivity).